Optimalisasi Program Police Goes To School Dalam Mengurangi Angka Pelanggaran Lalu Lintas Pelajar Oleh Unit Dikyasa Satuan Lalu Lintas Polres Tasikmalaya - Ardianto, Klinsmann Timotius (Indonesian Journal of Police Studies, 2020)
This research is motivated by the phenomenon of traffic violations committed by students in the law area of ​​the Tasikmalaya Regional Police due to student disorder in traffic on the highway. Therefore, a study aimed at describing the implementation of the Police Goes to School program carried out by the Tasikmalaya Police Traffic Unit, identified the factors that influence and describe the efforts made in optimizing the Police Goes to School program. Theories and concepts used by the author in answering problems are Management theory, 6M Management elements, Communication theory, Optimization concept, Traffic Violation concept, Dikmas Lantas concept, Kamseltibcar Lantas concept and Enculturation concept. This research was conducted with a qualitative approach and using a type of field research. The results of the study refer to the implementation of the Police Goes to School program in educating students to a minimum. Analysis of the implementation of the program according to the theory of Communication and 6M elements shows that the implementation of the Police Goes to School program is not running optimally in its implementation because there are still many traffic violations committed by students. The implementation of the Police Goes to School program between planned activities and implementation has not been well implemented. The findings of the study indicate that factors affecting the field of human resources are still limited, lack of budget, lack of facilities and infrastructure, less innovative methods and school targets that are not achieved are all obstacles to implementation. Based on the results of the study, the authors suggest that the Dikyasa Unit create more innovative activities to attract the attention of students, form the KADET LANTAS organization to make students as traffic safety agents and empower the public relations field by utilizing the use of social media.